Development of Novel High Gain DC-DC Converter Topology for Low Voltage DC Sources - Thangavelu , Shanthi; Umapathy , Prabha (Research and Developments in Engineering Research Vol. 6, 2023)
The aim of this chapter is to develop a new topology for high step-up non-isolated dc-dc converter for solar PV applications. The sources of electricity production such as coal, oil, and natural gas have contributed to one-third of global greenhouse gas emissions. It is essential to raise the standard of living by providing cleaner and more reliable electricity. The suggested high voltage gain converter topology has numerous benefits, including continuous input current, high gain with low duty ratio, and minimal voltage stress on the switches. The suggested converter's analytical waveforms are shown in both continuous and discontinuous modes of operation. Analysis of voltage stress is done. Additionally obtained are the converter's voltage gain and efficiency in the presence of parasitic components. The proposed high gain converter architecture is compared to recently reported high gain converter topologies in terms of performance. The test results from the proposed converter's simulation are used to validate the theoretical analysis. For the maximum duty ratio of 80%, the output voltage of 670 V is observed, and the voltage gain obtained is 14. Comparison of theoretical and simulation results are presented which validates the performance of the proposed converter. Comparison of theoretical and simulation results is executed which validates the working of the proposed converter. Therefore, the proposed converter is best suitable for grid connected as well as for standalone solar PV applications.